2016
DOI: 10.1371/journal.pone.0167917
|View full text |Cite
|
Sign up to set email alerts
|

Change in 18F-Fluoromisonidazole PET Is an Early Predictor of the Prognosis in the Patients with Recurrent High-Grade Glioma Receiving Bevacizumab Treatment

Abstract: BackgroundBevacizumab (BEV), a humanized monoclonal antibody, become a currently important chemotherapeutic option for the patients with recurrent glioma. The aim of this retrospective study is to investigate whether 18F-Fluoromisonidazole (FMISO) PET have the potential to detect BEV-resistant gliomas in the early-stage.MethodsWe reviewed the FMISO PET and MRI appearances before and 3 to 4 courses after BEV treatment on 18 recurrent glioma patients. FMISO accumulation was assessed by visual inspection and semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…17 18 F-FMISO PET is also thought to be useful for assessment of the response to treatment, such as radiation combined with temozolomide or bevacizumab for high-grade glioma, and for detecting changes in oxygenation, so the prediction map might be suitable for that purpose. 18,19 Although the cerebral cortex and basal ganglia were shown on the prediction map, these areas are easily recognized as normal structures by their shape, and can be excluded when we see a FLAIR image that shows the rough boundary of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 18 F-FMISO PET is also thought to be useful for assessment of the response to treatment, such as radiation combined with temozolomide or bevacizumab for high-grade glioma, and for detecting changes in oxygenation, so the prediction map might be suitable for that purpose. 18,19 Although the cerebral cortex and basal ganglia were shown on the prediction map, these areas are easily recognized as normal structures by their shape, and can be excluded when we see a FLAIR image that shows the rough boundary of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FMISO PET is also thought to be useful for assessment of the response to treatment, such as radiation combined with temozolomide or bevacizumab for high-grade glioma, and for detecting changes in oxygenation, so the prediction map might be suitable for that purpose. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, [ 18 F]FMISO PET has been used for monitoring the effects of antiangiogenic therapy with bevacizumab in patients with recurrent malignant glioma [132,133]. It was shown that patients who had a response in both contrast-enhanced MRI and [ 18 F]FMISO PET had significantly longer survival than patients who responded on MRI only [133].…”
Section: Pet Imaging Of Tumor Hypoxiamentioning
confidence: 99%
“…Using Zirkonium-89, the in vivo biodistribution of bevacizumab was shown. In another study the modulation of the hypoxic area within a tumor by bevacizumab was demonstrated by means of a hypoxia PET tracer [ 17 , 117 , 118 ]. Immune Modulation …”
Section: Cancer Cell Signaling Pathways – Figmentioning
confidence: 99%